Orality and textuality in the Iranian world: patterns of interaction across the centuries - Rubanovich, Julia (Jerusalem studies in religion and culture, 2015)
"The volume demonstrates the cultural centrality of the oral tradition for Iranian studies. It contains contributions from scholars from various areas of Iranian and comparative studies, among which are the pre-Islamic Zoroastrian tradition with its wide network of influences in late antique Mesopotamia, notably among the Jewish milieu; classical Persian literature in its manifold genres; medieval Persian history; oral history; folklore and more. The essays in this collection embrace both the pre-Islamic and Islamic periods, both verbal and visual media, as well as various language communities (Middle Persian, Persian, Tajik, Dari) and geographical spaces (Greater Iran in pre-Islamic and Islamic medieval periods; Iran, Afghanistan and Tajikistan of modern times). Taken as a whole, the essays reveal the unique blending of oral and literate poetics in the texts or visual artefacts each author focuses upon, conceptualizing their interrelationship and function. Contributors are: Frantz Grenet, Jo-Ann Gross, Charles G. Häberl, Galit Hasan-Rokem, Reuven Kiperwasser, Ulrich Marzolph, Margaret A. Mills, Ravshan Rahmoni, Karl Reichl, Julia Rubanovich, Shaul Shaked, Raya Shani, Dan Y. Shapira, Maria E. Subtelny, Gabrielle R. van den Berg, Yuhan S.-D. Vevaina, Naama Vilozny, Mohsen Zakeri, and Tsila Zan-Bar Tsur"--Provided by publisher